Challenges in Translating the Lyrics of the Song “Bojo Galak” by Pendhoza from Javanese into Indonesian: Tantangan Menerjemahkan Lirik Lagu “Bojo Galak” Karya Pendhoza dari Bahasa Jawa ke Bahasa Indonesia - Nugroho, Agus Digdo Nugroho (Kementerian Sekretariat Negara Republik Indonesia, 2025)
Translating dangdut koplo song lyrics presents its own challenges. Gender bias, red-herring fallacy, unclear meanings, and inequivalent popular Javanese terminologies to target language present challenges. For example, the lyrics of Pendhoza's song